Pengaruh Kepemimpinan Kepala Sekolah, Kinerja Guru dan Pelatihan Guru PAI Terhadap Implementasi Kurikulum Holistik Berbasis Karakter di SD Islam Plus Karakter - Lestari Oktarini, Shinta; Eka Citra, Desy (UIN Fatmawati Sukarno Bengkulu, 2023)
This research was motivated by the lack of supervision and guidance of the principal and some teachers still did not understand and implement in accordance with the PHBK curriculum. This study aims to: (1) Analyze the presence or absence of the influence of the principal's leadership on the implementation of the PHBK curriculum, (2) Analyze the presence or absence of the influence of PAI teacher performance on the implementation of the PHBK curriculum, (3) Analyze the presence or absence of the influence of PAI teacher training on the implementation of the PHBK curriculum, (4) Analyze the presence or absence of the influence of the principal's leadership, teacher performance and PAI teacher training on the implementation of the PHBK curriculum. Types of research What is used is a type of quantitative research with a survey approach. The results of the study: (1) There is an influence of the principal's leadership on the implementation of the PHBK curriculum at SD Islam Plus Karakter Kota Bengkulu which is shown in the t count (2.352) > t table (5% = 1.74) and at the significance level of 0.021 <0.05. (2) There is an influence of PAI teacher performance on the implementation of the PHBK curriculum at SD Islam Plus Karakter Kota Bengkulu which is shown in the t count (2,002) > t table (5% = 1.74) and at the Significance level of 0.036 <0.05. (3) There is an influence of PAI teacher training on the implementation of the PHBK curriculum at SD Islam Plus Bengkulu City Character shown in t count (3,094) > t table (5% = 1.74) and at a significance level of 0.003 < 0.05. (4) There is an influence of the principal's leadership, PAI teacher performance and PAI teacher training on the implementation of the PHBK curriculum at SD Islam Plus Bengkulu City Character shown in F count (3.684) > t table (5% = 3.20) and at the significance level of 0.032 < 0.05.